Tendencje rozwojowe popytu na zmechanizowany sprzęt domowy - Michalski, Eugeniusz (Wydział Prawa i Administracji UAM, 1967)
The first chapter dwells on planned purchases of mechanized home gadgets. The analysis rests on statistical polls covering 1577 home managements in the city of Wrocław, which have been chosen by lot method. The foreseen purchases of home gadgets in the years of 1966—1970 have been based on the analysis of the existing home equipment, intentions to buy them and the hierarchy of planned purchases. The second and third chapter describe the influence of age, vocation and sex of the head of family, the monthly income of the family's members and the numerical size of the family — on the villingness to procure mechanical home gadgets. The analysis of the variants of said factors has made it possible to grasp the scope of their influence on the development of demand for said gadgets. Chapter four contains the rsults of the assessment of the market (with respect to the supplies), the remarks about the shortcomings of the market and the propositions concerning a broader assortments of mechanical home gadgets. In the last chapter the author signalizes the phenomenon of inadequate supplies which do not meet the growing demand. A special survey of 10 retail shops has showed the intensity of unmet demand in the spring and summer season and the structure of motives which led to purchase resignations.
The tendencies in the development of demand for mechanized home gadgets